Addiction and responsability : An inquiry into the addictive mind - Seeburger, Francis F. (New Yor, U.S.A. : The Crossroad Publishing Company, 1993)
Interest in the subject of addiction has grown remarkably in the last few decades. Popular literature on addiction hgas multiplied phenomenally.
PART I: Being Addicted 1. The ecperience of addiction 2. The addictive mind PART II: Thinking about addiction 3. Defining addiction 4. Delimiting the scope of addiction 5. Classifying addiction PART III: 6. The essence of addiction 7. The meaning of addiction 8. The root of addiction PART IV: Responding to addiction 9. "Right effort"Towards addiction 10. Freedom from addiction: The nonaddictive mind 11. Addiction and responsibility
Includes bibliographical, references and index
Keywords: ADDICTION; DRUGS; ADDICTIONS - CAUSES